Water footprint of irrigated cotton production in Xinjiang under predicted climate change scenarios - Pengcheng TIAN; Zhiwei YUE; Xiangxiang JI; Ning YAO; Pute WU; La ZHUO (Frontiers of Agricultural Science and Engineering)
Xinjiang, one of China’s most water-scarce provinces, produces 25% of the world’s cotton. However, changes in water consumption of cotton production in Xinjiang under two climate change scenarios is unclear. This study considered three irrigation techniques (i.e., furrow, micro (drip) and sprinkler irrigation) and simulated the blue and green water footprints of cotton production in Xinjiang at a 5-arcmin grid level in response to climate change scenarios in the 2050s and 2090s. Taking the period 2000–2018 as the baseline, results showed that this footprint of cotton in Xinjiang for the baseline period was 4264 m3·t–1, with blue water accounting for 83%. Under climate change scenarios, Xinjiang was predicted to have an increasing drought trend and intensifying pressure on water resources. Owing to increased CO2 concentrations, the water footprint of cotton tended to decrease by 19.3% and 35.7% under two Shared Socioeconomic Pathway scenarios—SSP2-4.5, representing a moderate socioeconomic development path with lower emissions, and SSP5-8.5, indicating a scenario of high growth with higher emissions—respectively, for the 2090s. The blue water footprint was predicted to have an overall decrease. However, its proportion of the total would increase slightly, with the highest increase being 3.4%. The green water footprint was also predicted to have decreasing trend, with reductions of 33.7% (SSP2-4.5) and 47.2% (SSP5-8.5), respectively. Of the three irrigation techniques, sprinkler irrigation was predicted to have the greatest water conservation potential, with a reduction of up to 40.1%.